Unbalanced development: Regional disparity analysis in Serbia - Emilija Manić; ore Mitrović (Economic Themes, 2021)
The unbalanced regional development is one of the biggest socioeconomic challenges in Serbia. It is a multidimensional and multi-level regional imbalance that, according to almost all socioeconomic indicators, shows a growing trend in the first decades of the 21st century. This paper presents an analysis of the selected demographic, social, and economic indicators by using DEA methodology. The dynamic component of the studied imbalance was taken into account by calculating the Malmquist Productivity Index. The calculated index undoubtedly shows that there are differences between regions (not only between the northern and southern regions, but also within the regions themselves). The results also point out that the changes of the input usage efficiency have strongly influenced the ranks of the districts within the national territories.
Keywords: C5; R5; R10; R12; 330; regional imbalance; regional development; DEA analysis; Malmquist Productivity Index